Competition variation as a musical and choreographic form of competitive compositions of European and Latin American dances - Bugayets, Nataliya; Pinchuk, Olga; Hamivka, Alina (Professional Art Education, 2024)
The article reveals the meaning of the concept of "competition variation" as a specific form of competitive composition in sports dances in individual disciplines: European dances, Latin American dances, ten dances and Pro-Am.Methods & methodology. The research used such methods as search-analytical, structural-typological, comparative, prognostic and generalization, which made it possible to collect information on the chosen topic, analyze the similarities and differences of competitive compositions in choreography, determine further directions of development of competitive variations and forms of competitive compositions of European and of Latin American dances, summarize the conclusions.The scientific novelty consists in the representation of the definition of the concept of "competition variation of European and Latin American dances" as an imaginative, plotless choreographic work that embodies the gender interaction between a man and a woman in an artistic and plastic form, which was created according to the laws of drama and composition on the material of the corresponding European or Latin American dance taking into account the Rules for the competition, the defining feature of which is categorization, variation and cyclicity.Results. As a result of scientific research, the meaning of the concept of "variation" in music and choreographic art, in particular ballroom dance, was revealed both in the historical sense - a small virtuoso combination of steps and jumps performed solo, and in the modern sense as a changed or more complex figure that complements the main figures.Conclusions. It was established that the competition variation represents an imaginative, plotless choreographic piece that embodies the gender interaction between a man and a woman in an artistic and plastic form. It was found that it is created according to the laws of dramaturgy and composition on the material of the corresponding European or Latin American dance, taking into account the Rules for the competition, and it is proved that its defining feature is categorization (level of technical complexity), variation and cyclicity. It was found that each competitive composition has a corresponding musical and choreographic form, which integrates not only choreographic and plastic elements, visual and expressive means, compositional techniques, but also the tempo, dynamics and timbre of music, which are used as material for reproduction figurative and thematic emotional content. It was determined that the embodiment of the musical and choreographic form in sports dances is the competitive variation. It has been proven that European and Latin American dances are groups of five dances of different nature and origin that are standardized for training, amateur medal tests, professional exams and competitions. Thus, the competitive variation represents the musical and choreographic form in sports dances.
Keywords: sports dance; conceptual-categorical apparatus; European dances; Latin American dances; variation; musical and choreographic form; competitive variation